Maurice Line : a celebration of a lifetime in librarianship - McGrath, Mike, 1956-; Pilling, Stella (Interlending & document supply ;, 2005)
Maurice Line's first article (1952) was, in retrospect veryunexpectedly, on cataloguing - "The classification andarrangement of music scores". It was an excellentdiscussion of a difficult practical problem, and showedsigns of iconoclasm even then. His first substantial workwas "A bibliography of Russian literature in Englishtranslation". A professor of Russian history told merecently that it was one of the best English bibliographiesof Russian culture, retaining its usefulness 40 years on. Maurice never returned to Russia in his writings - but hisenthusiasm for Russian novels has persisted to t